2016
DOI: 10.3390/ijms17101693
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Tissue Distribution and Expression, and Potential Antiviral Effects of TRIM32 in the Common Carp (Cyprinus carpio)

Abstract: Tripartite motif-containing protein 32 (TRIM32) belongs to the tripartite motif (TRIM) family, which consists of a large number of proteins containing a RING (Really Interesting New Gene) domain, one or two B-box domains, and coiled coil motif followed by different C-terminal domains. The TRIM family is known to be implicated in multiple cellular functions, including antiviral activity. However, it is presently unknown whether TRIM32 of common carp (Cyprinus carpio) has the antiviral effect. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…3D; "Methods": Note 1), indicating a conserved antiviral activity in the C. hamatus genes. The antiviral activity found in these two genes is similar with those found in other fishes [31,32]. To be noticed, as many as 36 trim35 and trim39-like homologous genes are present in C. hamatus genome (Additional file 1: Fig.…”
Section: The Population-specific Selection Sweepssupporting
confidence: 70%
“…3D; "Methods": Note 1), indicating a conserved antiviral activity in the C. hamatus genes. The antiviral activity found in these two genes is similar with those found in other fishes [31,32]. To be noticed, as many as 36 trim35 and trim39-like homologous genes are present in C. hamatus genome (Additional file 1: Fig.…”
Section: The Population-specific Selection Sweepssupporting
confidence: 70%
“…Three reference genes, gapdh , beta actin and 18S , were tested for the stability of expression among all samples; as reflected in no significant differences between Selection and Control groups ( S6 Table ), all three genes exhibited a stable expression. On the basis of our previous experiences and published studies [ 101 , 102 ], we selected gapdh as the reference gene. Primers were designed using Primer Premier 5 software (Premier Biosoft, USA) on the basis of sequences of these ten genes obtained from the transcriptome data, and synthesized by the WCcgene company (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the expression patterns of trim16 and trim 25 in Nile tilapia ( Oreochromis niloticus ), the adtrims showed their highest expression levels in blood. The adtrim2 , adtrim8 , and adtrim23 genes were not only predominantly expressed in the blood, but also were highly expressed in the brain, head kidney, and muscle, which is same as other members of trims , such as trim8 in the orange spotted grouper ( Epinephelus coioides ), which is highly expressed in the kidney and brain, and trim32 in Common Carp ( Cyprinus carpio ), which shows significant expression in the brain and muscle (Huang, Yang, et al, ; Wang, Li et al, ). In addition, the trim genes are expressed widely in various tissues and organs in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the expression of white spotted bamboo shark trim35 in spleen increased after injection LPS (Zhang et al, ). Furthermore, the Common Carp trim32 was upregulated in response to Spring viremia of carp virus (SVCV) challenge in the spleen and kidney (Wang, Li et al, ). Although the expression changes vary in magnitude among the different trim genes, the pattern of expression in the spleen and kidney exhibited a similar profile.…”
Section: Discussionmentioning
confidence: 99%